Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT Wiharta Karya Agung Gresik - Nayaka Daksa Gardapati; Sulastri Irbayuni (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the effect of workload and work environment on the performance of employees at PT Wiharta Karya Agung Gresik. The sample used in this study was 90 workers in the production division at PT Wiharta Karya Agung Gresik. This study collects data through questionnaires distributed to workers in the production division at PT Wiharta Karya Agung Gresik. The variables determined by the researchers include: the independent variable is workload (X1), work environment (X2) and the dependent variable is performance (Y). This study uses analysis in the form of a partial least square (PLS) model, which is a method for constructing a model that can be assumed when there are several factors. The results of this study indicate that the high workload can delay the performance of employees and the environment from good work can encourage the performance of employees at PT Wiharta Karya Agung Gresik.